COMPARISON PHYTOCHEMICAL COMPOUNDS FROM TWO DIFFERENT SOLVENTS OF CRUDE CAPPARIS SPINOSA EXTRACTS - Manar F. jassim Al-khafagi,; Dina Yousif Mohammed, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
An experiment was conducted to evaluate different parts of the plant Capparis spinosa L. extracts for their phytochemical compounds by two different solvents (ethanol &hexane) . The current results showed the superiority of the ethanolic extracts by their quantity and quality of active compounds compared to the hexane extracts. The yield percentage of ethanolic Capparis spinosa L  extracts ranges between (3-31%), and color range between Dark brown, and olive with oily texture. Whereas, the yield of the hexane extract ranges between (1-27.9%) and it takes a longer time for extract with difficult to obtain, Ultimately, the results of the phytochemical analysis demonstrated the presence of numerous active compounds with higher degree of the sediment color in ethanol extracts such as: alkaloids, Phenols, Glycosides, Tannins, flavonoids and Saponin comparing with hexane extracts with lower color strength.